Rapid-onset clozapine-induced loss of glycaemic control: Case report. Issue 3 (May 2017) - Porras-Segovia, Alejandro; Krivoy, Amir; Horowitz, Mark; Thomas, George; Bolstridge, Mark; Ion, Dragos; Shergill, Sukhwinder S.
Abstract : Clozapine has proved to be an effective antipsychotic for the treatment of refractory schizophrenia – characterised by the persistence of symptoms despite optimal treatment trials with at least two different antipsychotics at adequate dose and duration – but its use is hampered by adverse effects. The development of clozapine-induced diabetes is commonly considered to arise as part of a metabolic syndrome, associated with weight gain, and thus evolves slowly. We present the case of an individual with refractory schizophrenia and metformin-controlled diabetes who developed rapid-onset insulin-dependent hyperglycaemia immediately after starting clozapine. Given the refractory nature of his illness, the decision was made to continue clozapine and manage the diabetes. This case supports the existence of a more direct mechanism by which clozapine alters glycaemic control, aside from the more routine slow development of a metabolic syndrome.